Effect of Different Extraction Methods on Quality Characteristics of Rapeseed and Flaxseed Oils - Shuzhen Wang; Jinying Wang; Guoxin Dong; Xia Chen; Shulin Wang; Feng Lei; Xuebing Su; Qin Bai (Journal of Food Quality)
This study reports the effect of roasted pretreatment combined with screw press, hydraulic press, and Soxhlet extraction methods on various quality indexes of rapeseed and flaxseed oils, including the oil yield, sensory indexes (color, smell, clarity, viscosity, and colligation score), physicochemical properties (acid value, peroxide value, saponification value, moisture and volatiles), major components (fatty acid composition and triglyceride composition), and minor components (volatile compounds, total phenols, and vitamin E contents). The results indicated that the oil yield, sensory indexes, physicochemical properties, fatty acid composition, volatile compounds, total phenol, and vitamin E contents in vegetable oils have been significantly affected by different extraction methods. The yields of rapeseed and flaxseed oils of Soxhlet extraction method were increased by 30.10%–73.90% and 6.30%–54.40%, respectively, compared with other treatment groups. In addition, roasted pretreatment significantly increased the yields of oils by 4.10%–25.00% and 6.70%–23.15%, respectively, compared with the untreated group. The contents of linolenic acid and vitamin E in rapeseed and flaxseed oils extracted from screw press method were higher. In particular, the linolenic acid content of cold-pressed rapeseed oil extracted by screw press increased by 1.50%–23.80% compared with other treatment groups. In addition, the contents of vitamin E in cold-pressed rapeseed oil and flaxseed oil obtained by screw press increased by 1.22%–78.91% and 3.00%–18.80%, respectively. The Soxhlet extraction could improve oil yield and total phenol content, but the quality of the oil was inferior due to high acid values (0.93–3.36 mg KOH/g) and peroxide values (0.70–5.23 meq O2/kg). Furthermore, the hydraulic press method could extract vegetable oils with excellent sensory scores. The roasted pretreatment gives the rapeseed and flaxseed oils a good smell. The major volatile compounds in rapeseed and flaxseed oils were aldehydes, acids, alcohols, heterocycles, and ketones. Different extraction methods and pretreatment had no significant effect on the compositions and contents of triglycerides. This study provides a basic understanding on the selection of appropriate oil extraction techniques for oil extraction at a large scale.